THE INFLUENCE OF LEADERSHIP AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN THE TRADE AND INDUSTRIAL SERVICES GOWA DISTRICT - Wardiena Nurul Zafiqa; Ahmad Ac; Ismail Rasulong (International Journal of Economic Research and Financial Accounting, 2024)
The aim of this research is a type of quantitative research with the aim of finding out the influence of leadership and work discipline on employee performance at the Gowa Regency Trade and Industry Service. This sample was taken from the Gowa Regency Trade and Industry Service. The type of data used in this research is quantitative data obtained from distributed questionnaires and is related to the problem being studied. The sampling technique in this research uses a saturated sampling technique formula. The number of samples processed in this research was 35 people. Data collection was carried out by observation and distribution of questionnaires. In this research, the data sources used in data collection include primary data and secondary data. The research instrument used in this research used the Likert scale method. Based on the research results obtained, they were processed using the Statistical Package for the Social Science (SPSS) application version 27. Based on the results of the research that has been carried out, it shows that leadership and work discipline have a positive and significant effect on employee performance.